1995
DOI: 10.1042/bj3070039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of granulocyte-macrophage colony-stimulating factor and tumour necrosis factor-α on tyrosine phosphorylation and activation of mitogen-activated protein kinases in human neutrophils

Abstract: The present study was undertaken to determine the identities and characteristics of proteins with molecular masses between 40 and 44 kDa whose tyrosine phosphorylation increases in human neutrophils following stimulation of these cells with tumour necrosis factor alpha (TNF-alpha) and granulocyte-macrophage colony-stimulating factor (GM-CSF). Immunoblotting results demonstrate that addition of GM-CSF to human neutrophils increases the tyrosine phosphorylation of two proteins with molecular masses of 42 and 44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 41 publications
5
39
1
Order By: Relevance
“…The MEK inhibitor, PD098059, showed a concentration-dependent inhibition in both of these assays. Waterman and Sha'afi [24] reported that GM-CSF induced time-and concentrationdependent tyrosine phosphorylation of p42 and p44 ERKs, whereas TNF-␣ only induced tyrosine phosphorylation of a 40-kDa protein, possibly p38 MAPK. Employing the same phosphorylation-specific antibodies used in this study, Zu et al [31] found that incubation of suspended human PMNs with 25 ng/mL TNF-␣ for 5 min failed to induce phosphorylation of ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The MEK inhibitor, PD098059, showed a concentration-dependent inhibition in both of these assays. Waterman and Sha'afi [24] reported that GM-CSF induced time-and concentrationdependent tyrosine phosphorylation of p42 and p44 ERKs, whereas TNF-␣ only induced tyrosine phosphorylation of a 40-kDa protein, possibly p38 MAPK. Employing the same phosphorylation-specific antibodies used in this study, Zu et al [31] found that incubation of suspended human PMNs with 25 ng/mL TNF-␣ for 5 min failed to induce phosphorylation of ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…As GM-CSF primes PMN functional responses [7,12] and stimulates ERK activity in PMNs [24,29,30], ERK activation by GM-CSF was compared between GM-CSF and TNF-␣. Using the in vitro kinase assay, GM-CSF stimulated maximal ERK activity at concentrations from 300 to 500 pM, and maximal stimulation occurred at 5 min and fell gradually though 30 min (data not shown).…”
Section: Activation Of Erks By Tnf-␣ Versus Gm-csfmentioning
confidence: 99%
See 2 more Smart Citations
“…These data demonstrate that an unidentified kinase or kinases cause cytosolic PLA, phosphorylation in platelets. Differential activation of p42/p44 MAP kinase and cytosolic PLA, phosphorylation has also been reported in macrophages [I31 and neutrophils [14]. Kramer et al…”
mentioning
confidence: 92%